Lice Infestations in Sheep and Goats in Kombolcha District, East Hararghe Zone, Oromia Regional State, Ethiopia - Derara Dejene Disasa (Veterinary Medicine International)
A cross-sectional study on ectoparasites of sheep (n = 134) and goats (n = 250) was conducted in Kombolcha district, east Hararge zone Oromia regional state, east Ethiopia, from November 2018 to April 2019 to determine the prevalence of major lice infestation of sheep and goats and the associated risk factors. Out of the examined animals (384), 56 (41.8%) sheep and 88 (22.9%) goats were infested with Damalinia and Linognathus species of lice, respectively. Ewes and does were 3.6 times more at risk for Damalinia ovis than rams and bucks, and young ones were 2.1 times more at risk than adults. Animals with poor body condition scores were 6.9 times more at risk for Linognathus species than those with good body condition small ruminants (P<0.05). The observed overall prevalence is generally relatively high which may result in enormous economic losses through decreased production and productivity, damages to the skin, and deaths of the animal which requires an immediate professional and governmental attention.